Augmenting inpatient treatment for post-traumatic stress disorder with a computerised cognitive bias modification procedure targeting appraisals (CBM-App): protocol for a randomised controlled trial. Issue 6 (30th June 2018) - Woud, Marcella L; Blackwell, Simon E; Cwik, Jan C; Margraf, Jürgen; Holmes, Emily A; Steudte-Schmiedgen, Susann; Herpertz, Stephan; Kessler, Henrik
Abstract : Introduction: Influential theories of post-traumatic stress disorder (PTSD) suggest that dysfunctional appraisals of trauma play a key role in the maintenance of symptoms, and this suggestion is increasingly supported by research. Experimental studies have indicated that a simple computerised cognitive training procedure, here termed cognitive bias modification-appraisals (CBM-App), can modify trauma-relevant appraisals and reduce analogue trauma symptoms among healthy volunteers. This suggests the possibility that CBM-App could improve outcomes in PTSD via targeting the key process of dysfunctional appraisals, for example, if applied as an adjunct to treatment. Methods and analysis: The study is a randomised controlled trial with two parallel arms. It is planned to randomise 80 patients admitted for treatment for PTSD to an inpatient treatment clinic to complete either sessions of CBM-App or a sham-training control condition, the peripheral vision task. Both interventions comprise eight sessions scheduled over a 2-week period and are completed in addition to the standard treatment programme in the clinic. Outcome assessment occurs pretraining, after 1 week of training, post-training, at discharge from the inpatient clinic and 6 weeks and 3 months postdischarge. The primary outcome is dysfunctional trauma-relevant appraisals at post-training, measured using a scenario completion task. Secondary outcomes include symptom measures and hair cortisol. Outcome analyses will be primarily via mixed linear models and conducted with both intention to treat and per protocol samples. Ethics and dissemination: The trial has been approved by the Ethics Committee for the Faculty of Psychology, Ruhr-Universität Bochum (approval no 204) and the Ethics Committee for the Faculty of Medicine, Ruhr-Universität Bochum (approval no 15-5477). Results will be published in peer-reviewed journals and will inform future clinical and experimental studies into targeting maladaptive appraisals for the reduction of PTSD symptoms. Trial registration number: NCT02687555 .